Pemanfaatan Daun Kelor untuk Meningkatkan Produksi ASI - Hani Septiani; Dini Ariani; Nadia Hanifa; Nayundha Indicasari Putri (Daarul Ilmi: Jurnal Pengabdian Kepada Masyarakat, 2023)
Introduction: Breast milk is one of the main sources for newborns because it contains nutrients that are important for the growth and development of babies, one of which is to increase the body's immunity against disease. This nutritional factor needs to be considered by a mother in the process of breastfeeding Objective: The purpose of this service is in the form of health education about the many benefits of Moringa leaves. The use of Moringa leaves is not only for pregnant women, but for nursing mothers, toddlers, and even other families can also consume Moringa leaves.Method: This public service is carried out by lecturers and students to the community with the target of pregnant women and mothers of toddlers at the Posyandu Pustu Linggasari in July 2022 with around 40 participants. Notification of this information is done through the distribution of leaflets related to the benefits of Moringa leaves. Result: The result of this PKM activity is an increase in knowledge regarding the use of Moringa leaves to increase breast milk production and how to process Moringa leaves. Conclusion: This community service activity increases the knowledge of pregnant women and mothers of toddlers. The next activity is an activity about utilizing Moringa leaves by processing Moringa leaves into snacks as an effort to vary food processing.